The Risk of Fractures Associated with Thiazolidinediones: A Self-controlled Case-Series Study - Douglas, Ian J.; Evans, Stephen J.; Pocock, Stuart; Smeeth, Liam (PLOS Medicine, 2009)
Ian Douglas and colleagues analyze records from the UK General Practice Research Database, and find that among individuals prescribed thiazolidinediones who develop a fracture, fractures are more common during periods of thiazolidinedione exposure than unexposed periods.